William Blackstone law and letters in the eighteenth century - Prest, Wilfrid R. 1940- (Oxford Univ. Press, 2008)
Lawyer, politician, poet, teacher and architect, William Blackstone was a major figure in 18th century public life, and pivotal in the history of law. Despite the influence of his work, Blackstone the man remains little known. This book sheds light on the life, work and society of a neglected figure.